PkM Kesehatan Reproduksi Perempuan Dalam Perspektif Ekonomi - Yenni Ariestanti; Yeny sulistyowati; Titik Widayati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Health and productivity are equally important and interconnected. Health is a primary asset. Without good health, achieving productivity becomes challenging. During the peak of the pandemic, funds were redirected from women's and girls' health to other life-saving services. There was also a lack of awareness and general prioritization. This led to a significant funding gap in women's healthcare. Furthermore, the lack of funding for women's health research means that specific challenges or diseases affecting women and girls remain unaddressed. They contribute economically and enrich their nation's wealth. Additionally, they play a crucial role in fostering intergenerational progress, thereby creating more opportunities for their children. An economy that neglects women and girls will widen the gender parity gap. Prioritizing the health of women and girls is a crucial path to building a healthier economy, society, and community. Identifying the issue, aiming to understand why women lack understanding regarding reproductive health issues linked to the post-pandemic economic perspective, is an effort to prioritize health, especially reproductive health. The implementation of Community Service Program (PKM) is carried out through an online webinar via Zoom Meeting link and YouTube on Saturday, February 25, 2023. This activity is in the form of a planned training in partnership with the Cipayung sub-district as part of the university's development efforts, involving an Obstetrician-Gynecologist doctor. The target audience includes lecturers, students, and the general public from all over Indonesia, with a total of 238 participants, including professors, students, nurses, midwives, and the public. Participants comprehend the provided material, engage in discussions, and pose questions about women's reproductive health from an economic perspective.Keywords: Community Service Program (PKM), Reproductive Health, Economy, Women.